Community Empowerment: Implementasi Mitigasi Bencana Dalam Mendukung Pembelajaran Pada Kurikulum Merdeka Belajar - Lucya Resta, Ichy; Juventa; Wiratama, Jarot (Jurnal Tiyasadarma, 2024)
Disaster resilience is being implemented by transferring knowledge about potential disasters in the surrounding areas, mitigation strategies, and information sources to teachers and students in schools, aimed at enhancing community capacity to support Kurikulum Merdeka Belajar. The Community Service Program (CSP) team presented information about potential disasters in the Province of Jambi, illustrated maps of potential disaster areas, and demonstrated the use of InaRisk. Evaluation was conducted through surveys after the activity to assess the level of understanding among teachers and students regarding disasters and participant attendance surveys were also conducted. The CSP activities achieved an average attendance rate of 96.15% of registered participants. The results showed that participants' knowledge regarding potential disasters in Jambi City and Province was considered good after participating in this activity, with an average score of 4,53. This reflects the values of Pancasila, which is a goal of the Kurikulum Merdeka Belajar.